Functional and Historical Perspective on the Nowruz Tradition - Menemencioğlu Temren, Belkıs (Journal of Alevism-Bektashism Studies, 2017)
This paper addresses the Nowruz tradition as a culture and tries to define it. Therefore, it begins with findings and evaluations about the perception and the place of the Nowruz tradition in different cultures. After this information about the Nowruz tradition, the place of the Nowruz in the Bektashi tradition is ascertained and evaluated by referring to the importance and the place of the Nowruz tradition in Turkish culture. The view of Bektashism, formed and developed in Turkish culture environment, on the Nowruz tradition is discussed on the basis of rituals. This paper which, finally, includes findings and evaluations about rituals and belief practices performed during the Nowruz within the Bektashi tradition, aims to draw the scientific community’s attention to the functional features of the Nowruz in the context of Nowruz rituals performed within the Bektashi tradition.
Keywords: Nowruz; Alevi; Bektashi; Babagan Bektashism; Turkish culture